2019
DOI: 10.1007/s10803-019-04346-w
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of Imagining Sounds and “Hearing” Music in Autism

Abstract: Individuals with autism spectrum disorder (ASD) reportedly possess preserved or superior music-processing skills compared to their typically developing counterparts. We examined auditory imagery and earworms (tunes that get "stuck" in the head) in adults with ASD and controls. Both groups completed a short earworm questionnaire together with the Bucknell Auditory Imagery Scale. Results showed poorer auditory imagery in the ASD group for all types of auditory imagery. However, the ASD group did not report fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…It is of note that this is not the first time a dissociation between voluntary and involuntary imagery has been reported in an atypical population. A similar dissociation was observed in a recent study with autistic participants; their BAIS self-ratings were found to be lower than controls in contrast to their earworm scores (Bacon et al, 2020). In fact, their earworm scores were slightly higher than those of their neurotypical counterparts.…”
Section: Discussionsupporting
confidence: 85%
“…It is of note that this is not the first time a dissociation between voluntary and involuntary imagery has been reported in an atypical population. A similar dissociation was observed in a recent study with autistic participants; their BAIS self-ratings were found to be lower than controls in contrast to their earworm scores (Bacon et al, 2020). In fact, their earworm scores were slightly higher than those of their neurotypical counterparts.…”
Section: Discussionsupporting
confidence: 85%
“…Autistic people find prosody difficult to hear, understand and reproduce [53]. It is widely reported that autistic people often exhibit music processing skills equal or superior to their typically developing counterparts [54]. Within the autism community, there are a few musical prodigies [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all of its capabilities are affected. People with ASD have greater precision in color processing [ 19 ] and greater processing of music than other typically developing people [ 20 ].…”
Section: Introductionmentioning
confidence: 99%